A rare case report of an ilio-psoas abscess due to entero-retroperitoneal fistula from gallstones post cholecystectomy. (February 2021) - Campioni-Norman, Daniel; Faulkner, Jack; Kumar, Lalit; Day, Andrew
Highlights: Ilio-psoas abscess due to gallstone entero-retroperitoneal fistulation post-cholecystectomy has not been reported previously. De-novo stone formation in the CBD can occur post-cholecystectomy and can lead to complications. Surgeons should consider gallstones as a differential in small bowel fistulation. Abstract: Introduction and importance: This is a novel case of a 50-year-old female presenting with several months of left iliac fossa pain, on a background of a cholecystectomy 5 years prior. The aetiology of her pain was an ilio-psoas abscess secondary to an entero-retroperitoneal gallstone fistula, a condition not previously reported in the literature. Case presentation: CT imaging revealed an abscess superior to the left psoas muscle, with a clear fistula to the small bowel and two calcified stones at the site of the fistula. The patient was managed operatively, with the fistula disconnected and a 5 cm section of small bowel disconnected. Clinical discussion: This is a novel case whereby a left sided iliopsoas abscess occurred due to entero-retroperitoneal fistulation of gallstones several years after the patient underwent laparoscopic cholecystectomy. Gallstone fistulation from within the small bowel does not appear to have previously been documented and the exact pathogenesis is unknown. Conclusion: Gallstones should remain an important, albeit rare, differential diagnosis of small bowel fistulation and abscess formation following cholecystectomy.